Biosynthesis and optimization of highly stable gold nanoparticles, nanoconjugates, nanodrug conjugates and chitosan nanoconjugates using medicinal plants - M. R. Kamala Priya (Bulletin of the National Research Centre, 2022)
Abstract Background In the present study, the medicinal plants were exclusively selected based on their significant anti-HIV and anticancer activities. The green synthesis of gold nanoparticles was carried out using the 15 medicinal plant extracts on reduction with chloroauric acid. The present study also focused on a novel pharmacognostic approach over the usage of plants source. The nanoparticle synthesized through medicinal plants possessed the potential therapeutic properties of the plants. The resultant nanoparticle carried the attributes of a nanomaterial alongside the phytoactivity. Results Initially, individual nanoparticle (NP) was synthesized through a single plant extract and studied for its effective anti-HIV and anticancer activity. Finally, a nanoconjugate (NC) comprising of the 3 extracts (trio extract) in one nanoparticle was synthesized. The nanoparticles which exhibited comparatively high anti-HIV and anticancer activity were chosen for the synthesis of nanoconjugate, thereby achieving a synergistic anticancer and anti-HIV activity. Further, a nanodrug conjugate (NDC) was prepared in combination of AuNPs and the chemotherapeutic drug, doxorubicin (Dox) for cancer and AuNPs with antiretroviral drug azidothymidine (AZT) for HIV. Conclusions A nanodrug conjugate helps to enhance the efficiency of the drug. The nanodrug conjugate brings about a combinatorial effect of the nanomaterials and the drug. Further, a biocompatible nanocarrier was developed as a conjugate with chitosan and gold nanoparticles using STPP as gelating agent for the drug doxorubicin. The synthesis reaction was optimized under various underlying parameters. The gold nanoparticles proved to be stable at high temperature and different buffers and ensured to be a safe option for bioassays and in vivo applications. Upon storing the synthesized AuNPs at different storage conditions, the nanoparticles were observed to be highly stable for a period of more than 48 months. The present study resulted in biosynthesis of highly stable gold nanoparticles using medicinal plant extracts as reducing and stabilizing agents.